Identifying effects of genetic obesity exposure on leukocyte telomere length using Mendelian randomization - Bangbei Wan; Ning Ma; Cai Lv (PeerJ, 2023)
Background Observational studies have shown that obesity is closely associated with leukocyte telomere length (LTL). However, the causal relationship between obesity and LTL remains unclear. This study investigated the causal relationship between obesity and LTL through the Mendelian randomization approach. Materials and Methods The genome-wide association study (GWAS) summary data of several studies on obesity-related traits with a sample size of more than 600,000 individuals were extracted from the UK Biobank cohort. The summary-level data of LTL-related GWAS (45 6,717 individuals) was obtained from the IEU Open GWAS database. An inverse-variance-weighted (IVW) algorithm was utilized as the primary MR analysis method. Sensitivity analyses were conducted via MR-Egger regression, IVW regression, leave-one-out test, MR-pleiotropy residual sum, and outlier methods. Results High body mass index was correlated with a short LTL, and the odds ratio (OR) was 0.957 (95% confidence interval [CI] 0.942–0.973, p = 1.17E−07). The six body fat indexes (whole body fat mass, right leg fat mass, left leg fat mass, right arm fat mass, left arm fat mass, and trunk fat mass) were consistently inversely associated with LTL. Multiple statistical sensitive analysis approaches showed that the adverse effect of obesity on LTL was steady and dependable. Conclusion The current study provided robust evidence supporting the causal assumption that genetically caused obesity is negatively associated with LTL. The findings may facilitate the formulation of persistent strategies for maintaining LTL.